The Effectiveness of Health Promotion Using Social Media on Adolescents' Knowledge of HIV/AIDS - Rus Andraini; Zusana A.Sasarari; Ayu Nurkhayati (Miracle Journal Get Press, 2025)
This study aims to determine the effectiveness of health promotion through social media in increasing adolescents' knowledge about HIV/AIDS. The sample consisted of 75 senior high school students selected using purposive sampling based on specific criteria. Data collection was conducted through pre-test and post-test questionnaires administered before and after the intervention within a specified time period. Bivariate analysis using paired t-tests showed that there was a significant increase in adolescents' awareness of HIV after the health promotion intervention via social media, with the average score increasing from 56.4 to 78.9 (p  0.001). In practical terms, the results of this study recommend that health promotion programmes among adolescents integrate social media as the main platform for delivering educational messages, paying attention to content quality, visual appeal, and interactive engagement.